Postęp badań fizjologicznych i genetycznych w zakresie reakcji drzew leśnych na niskie temperatury - Novokreshchenova, Maria; Kempf, Marta; Skowyra, Katarzyna (Leśne Prace Badawcze, 2019)
Forest trees are a great model for physiological and genetic studies of plant resistance to unfavorable environmental conditions, since the same species can successfully acclimate at different latitudes. Modern biology, such as genomics, transcriptomics, proteomics, etc., significantly facilitates these studies and accelerates the acquisition of new knowledge. This allows for a more effective implementation of conservation measures and the renewal of forest ecosystems. This review contains information on the latest scientific achievements in the field of acclimatization and tolerance to abiotic stresses, such as cold and frost, of forest trees. There is no doubt that in the course of evolution forest trees developed a complex and dynamic mechanism for controlling the entry into the winter dormancy stage, which allows woody plants to successfully survive in cold and freezing conditions and is initiated long before the beginning of winter. Studying the function of individual genes in forest tree species, however, remains an incredibly difficult task due to large genomes, specific development as well as the lack of standard techniques and routine procedures. In recent years, similarities between the well-studied genetic response to low temperatures of the model plant Arabidopsis thaliana and forest trees have been identified, which produced meaningful analogies and allows for issues of functional genetics to be addressed more effectively. The main goal of this work was to show that findings from forest tree genomics can be effectively used as a tool for the reproduction and protection of important tree species through the identification of the predisposition of specific populations to climate change and their adaptive capacity.